A Classical Ayurveda and Modern Review of Mutrashmariw S.R.Urolithiasis - Kanani, Dr.Dipa; Kumar Sharma, Dr. Rajesh; Sangani, Dr. Vipul; Varsadiya, Dr. Akash (Asian Journal of Pharmaceutical Research and Development, 2024)
The sign and symptoms as well as morphology of stone found in Mutrashmari are similar to that of Urolithiasis.In Shushruta Samhita Ashmari included in Ashtamahagada due to its notorious nature and reluctant to cure.Urolithiasis is third most common affliction of the urinary tract,exceeded only by UTI and BPH.The classical symptoms of Ashmariis pain with obstruction of urine.It is one of the common disease conditions worldwide and it is found that Ashmarirecurs in spite of Surgical and Palliative intervention which shows the importance of diet and lifestyle in the manifestation of Mutrashmari. Hence it is very important to know all the aspect of this urinary problem so,that it can be nipped in the bud.